Correction: Composition design, electrical properties, and temperature stability in (1 − x)K0.44Na0.56Nb0.96Sb0.04O3-xBi0.45La0.05Na0.5ZrO3 lead-free ceramics. Issue 19 (18th March 2020) - Ma, Jian; Wu, Juan; Wu, Bo
Abstract : Correction for 'Composition design, electrical properties, and temperature stability in (1 − x )K0.44 Na0.56 Nb0.96 Sb0.04 O3 - x Bi0.45 La0.05 Na0.5 ZrO3 lead-free ceramics' by Jian Ma et al., RSC Adv., 2018, 8, 29871–29878.